2016
DOI: 10.18632/oncotarget.10023
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-187 inhibits tumor growth and invasion by directly targeting CD276 in colorectal cancer

Abstract: Aberrantly expressed microRNAs contribute to the initiation and progression of human cancers. However, the underlying functions of microRNA-187 (miR-187) in colorectal cancer (CRC) remain largely unexplored. Here, we demonstrated that miR-187 was significantly down-regulated in CRC tissues and cell lines compared to their normal counterparts. By Kaplan-Meier analysis, we revealed that decreased miR-187 expression was closely associated with shorter overall survival and relapse-free survival of patients with CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
(40 reference statements)
4
30
0
Order By: Relevance
“…Aberrant miRNA expression has been reported to contribute to tumorigenesis and cancer progression in several types of human cancer (21)(22)(23). In the present study, the expression of miR-25-3p was revealed to be downregulated in OS tissues and cell lines compared with adjacent non-tumor bone tissues and normal osteoblasts, respectively.…”
Section: Discussionsupporting
confidence: 45%
“…Aberrant miRNA expression has been reported to contribute to tumorigenesis and cancer progression in several types of human cancer (21)(22)(23). In the present study, the expression of miR-25-3p was revealed to be downregulated in OS tissues and cell lines compared with adjacent non-tumor bone tissues and normal osteoblasts, respectively.…”
Section: Discussionsupporting
confidence: 45%
“…Among the evaluated studies, 49 demonstrated the downregulation of miR-199b 47, 48 , miR-6852 106 , miR-302c 67 , miR-466 68 , miR-650 123 , miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-296 73 , miR-187 124 , let-7a-5p 98 , miR-132 99 , miR-206 100 , miR-148a 125 , miR-33b 76 , miR-99b-5p 120 , miR-154 78 , miR-217 126 , miR-149 79 , miR-194 80 , miR-7 56 , miR-24-3p 54 , miR-29b 127 , miR-15a 34 , miR-16 34, 36 , miR-204-5p 128 , miR-96-5p 121 , miR-193a-5p 108 , miR-100 81 , miR-133a 41 , miR-139-5p 129 , miR-124-5p 130 , miR-335 82 , miR-378 101 , miR-126 40 , miR-378a-3p 58 , miR-378a-5p 58 , miR-218 83 , miR-138 110 , miR-625 111 , miR-212 112 , miR-124 131 , miR-22 49 , miR-133b 39 , miR-193a-3p 104 , miR-195 113 and miR-30c 103 associated with worse prognosis (lower overall survival) of CRC patients. Fifty-six studies identified the upregulation of miR-181a 3133 , miR-182 43, 44 , miR-1296 84 , miR-888 64 , miR-28-5p 132 , miR-183 45, 46 , miR-200c 114 , miR-34a 133 , miR-15a-5p 134 , miR-181c 135 , miR-24-3p 53 , miR-16 35 , miR-7 55 , miR-96 86 , miR-1260b 115 , miR-20a-5p 63 , miR-517a 87 , miR-503 136 , miR-106b 88 , miR-211 137 , miR-320e 89 , miR-592 90 , miR-196a 57 , miR-196b 57 , miR-376a …”
Section: Resultsmentioning
confidence: 99%
“…In total, 17 studies demonstrated the downregulation of 18 miRs associated with worse disease free-survival such as miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-22 50 , miR-296 73 , miR-199b 47 , miR-187 124 , let-7a-5p 98 , miR-132 99 , miR-29b 127 , miR-15a 34 , miR-16 34 , miR-34a-5p 65 , miR-193a-5p 108 , miR-138 110 , miR-126 8 , miR-212 112 and miR-124 131 . Twenty-one studies associated the upregulation of miR-888 64 , miR-28-5p 132 , miR-183 45 , miR-200c 114 , miR-34a 133 , miR-15a-5p 134 , miR-181c 135 , miR-24-3p 53 , miR-16 35 , miR-96 86 , miR-1260b 115 , miR-20a-5p 63 , miR-517a 87 , miR-503 136 , miR-106b 88 , miR-320e 89 , miR-196a 57 , miR-196b 57 , miR-224 51 , miR-494 61 , miR-181a 32 , miR-21 25, 26, 30 and miR-155 30 with worse disease free-survival.…”
Section: Resultsmentioning
confidence: 99%
“…This human miR-204-5p is important due to targets the antiapoptotic protein Bcl-2 in prostate cancer cells [100]. In addition, decreased expression of miR-187 was associated with reduced overall survival and relapse-free survival of patients with colorectal cancer [101]. Other miRNAs can act as tumor suppressors, miR-143 in human prostate cancer was reduced by targeting hexokinase 2 and represents another potential therapeutic target [102].…”
Section: Mirnas In Cancermentioning
confidence: 99%